PEMANFAATAN PARTIKEL TEMPURUNG KEMIRI SEBAGAI BAHAN PENGUAT PADA KOMPOSIT RESIN POLIESTER - Harnowo Supriadi (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Lampung, 2012)
Abstract The objective of the research is to investigate the effect of composition ratio of polyester as matrix and Aleurites moluccana willd particles on mechanical properties (hardness,flexure strength and tensile strength) of composite.This experimental research used Aleurites moluccana willd particles as reinforced material and polyester as resin.The instrument for the research were universal testing machine (UTM), hardness testing mac hine. This research had been performed by making variation of composition ratio of resin and Aleurites moluccana willd particles (30 % :70%, 40% :60 %, 50 % : 50% and 60% :40%).The result of this research show that the maximum hardness of composite was54,1 HRL. The maximum flexure strength was 33,62 N/mm2 and the maximum tensile strength was 16,97 N/mm2. The maximum value of hardness, flexure strength and tensile strength had been achieved on composition ratio 40 % :60 %.Keywords : Aleurites moluccana Willd particles, Aleurites moluccana willd particles, polyester resin, hardness, flexural strength, tensile strength.